Propensity score analysis of high-dose rate brachytherapy, immune checkpoint inhibitors, and docetaxel in second-line advanced NSCLC treatment - Ran Cui; Hong Su; Yan Jiang; Xinlin Yu; Yu Liu (Scientific Reports)
Abstract This study evaluated the efficacy and safety of combining high-dose-rate brachytherapy, immune checkpoint inhibitors, and docetaxel as second-line treatment for advanced NSCLC, given the poor prognosis after first-line therapy. We conducted a single-center, retrospective, propensity score-matched study comparing HDR brachytherapy plus ICIs and docetaxel (study group) versus ICIs plus docetaxel (control group) in patients with advanced NSCLC who progressed after prior treatment without known driver gene mutations or uninvestigated mutation status. After propensity score matching, 21 patients were included in each group. The study group had a higher ORR (42.9% vs. 28.6%). Median OS was 18.6 months for the study group and 12.8 months for the control group (HR 0.45, 95% CI 0.20–0.85, P = 0.042). Median PFS was 8.6 vs. 5.6 months (HR   0.29, 95% CI 0.15–0.55, P < 0.001). The DCR was higher in the study group (71.4% vs. 61.9%). Treatment-related AEs were manageable, with no significant increase in grade 3/4 toxicities in the study group. Results suggest that combining high-dose rate brachytherapy, immune checkpoint inhibitors, and docetaxel may improve survival and response rates in advanced NSCLC after first-line therapy. Prospective randomized trials are necessary to confirm these findings and validate the strategy’s effectiveness.